Outpatient primary care cardiology referrals: Referral patterns, risk stratification and clinical outcomes - Yi Yi Chua; Yilin Jiang; Sinead Zhen Wang; Ian Phoon; Khung Keong Yeo; Terrance Siang Jin Chua; Jonathan Yap (Proceedings of Singapore Healthcare)
Introduction With an increasing burden of cardiovascular disease, there has been rising demands for outpatient cardiology services. In this study, we reviewed the cardiology referral patterns from primary care to a tertiary cardiac centre, and evaluated their longer term clinical outcomes based on referral symptomatology as well as risk stratification. Methods Consecutive outpatients referred from primary care to a national cardiac centre between March 2015 to December 2020 were included. Patients with known coronary artery disease (CAD) were excluded. Chest pain patients were stratified by pre-test probability (PTP) of obstructive CAD using chest pain risk scores and the rest by age and sex. Outcomes studied included mortality and major adverse cardiovascular events (MACE). Results A total of 33,244 patients (11,865 chest pain, 3427 palpitations, 2844 dyspnoea) were included. In patients with chest pain, the 3-year mortality and MACE rates were 1.25% and 3.19% respectively. Patients with higher PTP of CAD demonstrated significantly higher rates of adverse events. In patients with palpitations, the 3-year mortality and MACE rates were 0.86% and 1.55% respectively. Males aged >65years had significantly higher risk of 3-year mortality ( p < .00.5). In patients with dyspnoea, the 3-year mortality and MACE rates were 3.34 and 4.44% respectively. Subsets of younger age and/or female sex had lower rates of adverse events. Conclusions While long term adverse clinical outcomes were generally low in this stable outpatient cohort, risk stratification allowed for identification of an even lower risk subset of patients for whom additional testing may potentially not yield incremental clinical benefit.